1990
DOI: 10.1002/pd.1970101004
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and significance of cystic hygroma in the first trimester

Abstract: Thirty cases of cervical cystic hygroma were diagnosed in the first trimester of pregnancy. Karyotype analysis was available in 29 (97 per cent). Fifteen (52 per cent) had a chromosomal abnormality. The ultrasound appearance was described as posterior cervical, lateral cervical, or cervical hygroma with hydrops. Of the 14 euploid embryos, six were electively aborted, two are undelivered, and six have been delivered as phenotypically normal infants. In cases in which the chromosomes were normal and the pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0
8

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 24 publications
6
57
0
8
Order By: Relevance
“…[13] diagnosed cervical cysts above 2.5-3 mm in diameter as cystic hygroma, we used a discriminatory diameter of 5 mm to avoid any pitfalls and to differentiate between pathological and physiological variation [4,8,14,15]. Another cause might be due to the fact that cases with chromosomal aberrations, which were generally terminated in other studies [5,12,13], were conservatively observed without any intervention in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[13] diagnosed cervical cysts above 2.5-3 mm in diameter as cystic hygroma, we used a discriminatory diameter of 5 mm to avoid any pitfalls and to differentiate between pathological and physiological variation [4,8,14,15]. Another cause might be due to the fact that cases with chromosomal aberrations, which were generally terminated in other studies [5,12,13], were conservatively observed without any intervention in our study.…”
Section: Discussionmentioning
confidence: 99%
“…According to Bronshtein et al [13], non-septated hygroma may represent a temporary accumulation of lymph due to incomplete obstruction of lymphatic drainage and actually most of the non-septated hygroma in their report were transient, indicating that a lack of septation might not be a pathological situation. Cullen et al [4], Shulman et al [5] and Brumfield et al [19], on the other hand, concluded that it is useless to evaluate septation in the prediction of fetal prognosis. Our results coincide with the latter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A partir do início da década de 1990, vários trabalhos associaram a presença de uma quantidade anormal de fluido na região da nuca fetal, no primeiro trimestre da gestação [translucência nucal (TN) aumentada], com um aumento do risco de cromossomopatias [1][2][3][4][5][6][7][8] . Diferentes mecanismos fisiopatológicos foram propostos para explicar uma TN aumentada no fim do primeiro trimestre da gestação, entre eles as disfunções cardíacas, as anormalidades na matriz extracelular, o desenvolvimento anormal do sistema linfático, as limitações dos movimentos fetais, a anemia fetal ou a hipoproteinemia e as infecções fetais 5,9,10 .…”
Section: Introductionunclassified